Comparison of bioelectrical impedance analysis and magnetic resonance imaging for the quantification of fat mass - Forde, Cuisle (ClinMed International Library, 2015)
Introduction: Body composition is a key determinant of health. Many methods, including bioelectrical impedance analysis (BIA), are available to estimate body composition; however the validity of such methods varies greatly. The aim of this cross sectional study was to investigate the accuracy of the Tanita MC-180MA BIA machine in the quantification of fat mass through comparison with magnetic resonance imaging (MRI). Methods: Ten young healthy volunteers (aged 24.4, SD 3.8 years) underwent BIA and MRI. Fat mass quantification was generated by the system software of the MC-180MA through the use of prediction equations and impedance data, and through the use of a bespoke application developed for use with MRI output. Fat mass results for the lower limbs and torso were analysed using correlation, t-test and Bland and Altman analysis.Results: Strong correlation was observed however there was a significant difference between assessment methods for fat mass in the lower limb and in the lower limbs and torso combined (p=0.002 and p=0.013 respectively). Bland and Altman plots showed large limits of agreement spanning up to 54% of the overall mean and significant bias for measurement of fat mass in the lower limbs (2.2kg) and torso and lower limbs combined (2.6kg). Conclusions: When compared to results obtained during MRI, BIA significantly underestimated fat mass. Overall, accuracy was poor and it can be concluded that BIA showed poor agreement with MRI in the quantification of fat mass.
PUBLISHED
Keywords: Fat; Adiposity; Torso; Assessment